In-depth spectral characterization of antioxidative (1,3)-β-D-glucan from the mycelium of an identified tiger milk mushroom Lignosus rhinocerus strain ABI in a stirred-tank bioreactor - Ahmad Usuldin S.R.; Mahmud N.; Ilham Z.; Khairul Ikram N.K.; Ahmad R.; Wan-Mohtar W.A.A.Q.I. (Elsevier Ltd, 2024)
Indexed by Scopus